Practical guide to studying history skills and approaches - Loughran, Tracey (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"An introduction to the fundamental skills and principles underpinning historical research and writing, and to the different contexts in which history is produced and consumed"-- Provided by publisher.